2015
DOI: 10.1186/s12961-015-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Can contracted out health facilities improve access, equity, and quality of maternal and newborn health services? Evidence from Pakistan

Abstract: BackgroundThe case of contracting out government health services to non-governmental organizations (NGOs) has been weak for maternal, newborn, and child health (MNCH) services, with documented gains being mainly in curative services. We present an in-depth assessment of the comparative advantages of contracting out on MNCH access, quality, and equity, using a case study from Pakistan.MethodsAn end-line, cross-sectional assessment was conducted of government facilities contracted out to a large national NGO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 13 publications
0
35
0
1
Order By: Relevance
“…Participants in our study also perceived the success of existing PPP initiatives as important facilitator for the provincial government to be interested in adopting the PPP policy. Previous studies have also indicated that BHUs under the PPHI management perform better than government run BHUs 12,15,26 . For example, Tanzil et al 12 compared functioning of two BHUs in Sindh, one administered by PPHI and the other was led by government.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Participants in our study also perceived the success of existing PPP initiatives as important facilitator for the provincial government to be interested in adopting the PPP policy. Previous studies have also indicated that BHUs under the PPHI management perform better than government run BHUs 12,15,26 . For example, Tanzil et al 12 compared functioning of two BHUs in Sindh, one administered by PPHI and the other was led by government.…”
Section: Discussionmentioning
confidence: 96%
“…This article is based on a qualitative study carried out to explore stakeholder perspectives on PPP in healthcare service delivery in Sindh province of Pakistan including the reasons for adopting such policies, and the barriers for its implementation. Previous studies conducted in Pakistan have compared performance of government administered health facilities with those run by PPP 12,26,27 . Studies have also identified the challenges in the wider policy context for PPP implementation in the healthcare sector in Pakistan 28,29 .However, there is a dearth of research about stakeholder perspectives on factors that act as barriers in implementation of PPP in healthcare service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…While majority of the published literature including from Pakistan has focused on contracting out of primary healthcare facilities (22,24,26), this study has assessed both primary and secondary healthcare facilities. Present study shows that most of the improvement in service utilization, health workforce, drugs, equipment and supplies and infrastructure is seen at secondary healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…5 Improved water and sanitation are accessible to 96.5% of urban and 86.5% of rural areas. 6 However, only 24.5% of the urban and 21.4% of the rural population use piped water. About 96% of urban and 81% of rural households have access to improved sanitation.…”
Section: Provincial Socioeconomic and Health Sector Context Sociomentioning
confidence: 99%
“…The report suggests that most of the limitations encountered arise from the unsupportive context in which the model has operated and the weakness of the contracting instrument and of the contractor's capacity for contract management and M&E. Other studies looking at other projects have reached similar conclusions. 6 In spite of some limitations in the number, scope, and methodological design of some evaluations, available evidence suggests that these experiences of health PPPs or contracting out health service provision have been mostly successful. However, the DOH senior staff do not necessarily support these conclusions, and there is widespread resistance to these innovative models both within DOH and in society at large.…”
Section: Contracting Out For Primary Health Care and Hospital Servicesmentioning
confidence: 99%